The Relationship Between Emotional Intelligence and Burnout Levels Among Architecture Students - Yasemin Erbil; Dilek Murat; Filiz Şenkal Sezer (Megaron, 2016)
This study investigated the relationship between emotional intelligence (EI) and burnout among architectural students. The sample of the study included 35 4th year students in the Architecture Department. In the study the Emotional Quotient Inventory (EQ-i) of Bar-On was used to measure the emotional intelligence profile, and Maslach Burnout Inventory (MBI) of Maslach was used to measure the state of burnout. The EI level of architecture students was found upper intermediate with a score of 3,63/5. No relationship was found between the EI level of students and their gender, habitation, employment and financial welfare levels. The burnout status of architecture students was defined as intermediate with a score of 2,66/5. No relationship was found between the burnout status of students and their gender, habitation, employment and financial welfare levels. The statistical analysis of the data has revealed a strong statistically significant relationship, in the same direction between the emotional intelligence levels of the students and their burnout status. The study has also revealed a strong and statistically significant relationship between the burnout status and general mood and stress management subscales of emotional intelligence